Process and outputs from a community codesign workshop on reducing impact of heat exposure on pregnant and postpartum women and newborns in Kilifi, Kenya - Lusambili, Adelaide; Khaemba, Peter; Agoi, Felix; Oguna, Martha; Nakstad, Britt; Scorgie, Fiona; Filippi, Veronique; Hess, Jeremy; Roos, Nathalie; Chersich, Mathew; Kovats, Sari; Luchters, Stanley (Frontiers in Public Health, 2023)
Background Ambient heat exposure is increasing due to climate change and is known to affect the health of pregnant and postpartum women, and their newborns. Evidence for the effectiveness of interventions to prevent heat health outcomes in east Africa is limited. Codesigning and integrating local-indigenous and conventional knowledge is essential to develop effective adaptation to climate change. Methods Following qualitative research on heat impacts in a community in Kilifi, Kenya, we conducted a two-day codesign workshop to inform a set of interventions to reduce the impact of heat exposure on maternal and neonatal health. Participants were drawn from a diverse group of purposively selected influencers, implementers, policy makers, service providers and community members. The key domains of focus for the discussion were: behavioral practices, health facilities and health system factors, home environment, water scarcity, and education and awareness. Following the discussions and group reflections, data was transcribed, coded and emerging intervention priorities ranked based on the likelihood of success, cost effectiveness, implementation feasibility, and sustainability. Results Twenty one participants participated in the codesign discussions. Accessibility to water supplies, social behavior-change campaigns, and education were ranked as the top three most sustainable and effective interventions with the highest likelihood of success. Prior planning and contextualizing local set-up, cross-cultural and religious practices and budget considerations are important in increasing the chances of a successful outcome in codesign. Conclusion Codesign of interventions on heat exposure with diverse groups of participants is feasible to identify and prioritize adaptation interventions. The codesign workshop was used as an opportunity to build capacity among facilitators and participants as well as to explore interventions to address the impact of heat exposure on pregnant and postpartum women, and newborns. We successfully used the codesign model in co-creating contextualized socio-culturally acceptable interventions to reduce the risk of heat on maternal and neonatal health in the context of climate change. Our interventions can be replicated in other similar areas of Africa and serve as a model for co-designing heat-health adaptation.